LEADERS AND PROJECTS - COMMON ISSUES - A. Vacar (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This article is a small part of a long empirical and practical research and it began from the necessity of models to be followed in organizations and the way they can generate that expected behavior from others. Nowadays, projects seem to be the modern way of doing things in organizations because of their advantages. The article tries to present common issues between leaders and projects, both of them being as determinant factors for organizational success.